Menisco-ligamentous injuries of knee joint: Can ultrasonography serve as an effective screening modality? - Farooq Mir; Zahoor Raina; Omair Shah; Tariq Gojwari; Irfan Robbani; Tahleel Shera (PAGEPress Publications, 2021)
The aim is to calculate sensitivity, specificity and diagnostic accuracy of Ultrasonography (USG) as a screening modality in evaluation of Menisco- Ligamentous injuries of knee joint with Magnetic Resonance Imaging (MRI)as gold standard for comparison.Patients with clinically suspected Menisco-Ligamentous injurieswere evaluated by USG initially followed by MRI on the same day. A total of 60 patients (50 males, 10 females) underwent USG and MRI. USG was done using high frequency probe (9-14 Hz) and all the injuries noted. USG of the normal knee was done for comparison. MRI with trauma protocol sequences was done on the same day. The accuracy of USG and MRI in diagnosis of menisco-ligamentous injuries was compared. Majority of the patients (50%) belonged to age group of 21-40 years. Most common injuries seen were medial meniscal tear followed by medial collateral ligament injury. The strength of agreement between USG and MRI was good with Diagnostic accuracy of USG ranging from 83.3% to 95% for different meniscal/ligamentous injuries.USG is an effective imaging modality with high accuracy in diagnosing menisco-ligamentous injuries. USG can act as an effective screening modality in closed knee trauma for evaluation of menisco- ligamentous injuries especially in resource constrained regions owing to its easy availability, portability and lower cost. MRI can be reserved for patients with suspicious USG and clinical findings.